VDBP, VDR mutations and other factors related with vitamin D metabolism may be associated with type 1 diabetes mellitus - DİNÇER YAZAN, CEYDA; HAKLAR, GONCAGÜL; ŞİRİKÇİ, ÖNDER (C M B ASSOC, 2018)
Type 1 diabetes mellitus (T1DM) is an insulin dependent autoimmune disorder resulting the progressive destruction of pancreatic beta cells. Another possible factor considered to be related with T1DM is vitamin D deficiency. Therefore in this study it was aimed to investigate the associations between T1DM, vitamin D binding protein (VDBP) and vitamin D receptor (VDR) gene mutations which are related with vitamin D metabolism. Fifty five T1DM paitents and 40 healthy volunteers were recruited to the study. FokI (rs2228570), BsmI (rs1544410) mutations in VDR; rs4588 and rs7041 polymorphisms in VDBP were investigated with real-time polymerase chain reaction (RT-PCR). Other risk factors related with T1DM were also investigated. Results were evaluated statistically. Statistically significant relations were found in glucose, HbA1c, TSH, higher 25[ OH] D, free vitamin D, calcium, albumin, log25[ OH] D, retinopathy, higher than 30 mg/day microalbuminuria in T1DM patients. Also statistically significant association was found between C allele in Fok1 and T1DM in patients. When the relation between the risk factors and mutations were investigated, it was found that VDBP, free vitamin D and bioactive vitamin D were significantly associated with rs7041 mutation in VDBP whereas HDL was significantly associated with rs2228570 mutation in VDR. Other studies with larger data sets may demonstrate more reliable statistical results to rule out genotype-phenotype correlations of the
Keywords: T1DM; VDR; VDBP; RT-PCR; Vitamin D deficiency; D-BINDING PROTEIN; D-RECEPTOR GENE; 25-HYDROXYVITAMIN D; POLYMORPHISMS; RETINOPATHY; CHILDREN; RISK; SUSCEPTIBILITY; DISEASE; IMPACT